CONSTRUCTING ENGLISH VOCABULARY TESTS IN INSTAGRAM FOR 10TH GRADE STUDENTS OF VOCATIONAL HIGH SCHOOL - Labitta Khairunnisa; Hanip Pujiati (Universitas Negeri Manado, 2021)
In consequence of pandemic COVID-19, all the educational activities are moved to home or we know as distant learning. Teachers need to be able to adapted the technology especially social media to support educational activities. Instagram has many functions, which are: create accounts, post pictures or 60 second videos, add captions, apply filters, add locations, add hashtags, add comments, like other contents, browse and follow other accounts. Instagram has many features to be utilized to support educational activities, including for constructing English test especially in Vocabulary. Vocabulary is a core aspect in English language testing. This study aims to construct English Vocabulary test in Instagram for 10th grade students of Vocational High School and to find out the characteristics of appropriate English Vocabulary test for 10th grade students of Vocational High School constructed in Instagram. This study used Research and Development method. The researcher procedures are: researching and collecting information, planning (elaborating literature reviews), designing the draft of Vocabulary test or constructing the tests, having the test review by the experts, revising the test, conducting a try-out of the test, analysing the test in terms of level of difficulties, designing final test. The respondents of this study were 36 students of 10th grade from Multimedia 1 class in 40 Vocational High School Jakarta. The findings show that (1) The topics of English Vocabulary test in Instagram are introducing self/someone, congratulating and complementing, intentions, descriptive text, giving announcement, recount text, narrative text and past events, 2) The test types are true-false, multiple choices, short-answer and making a sentence, (3) The medium level of difficulty is used in this test. The English Vocabulary test for 10th grade students of Vocational High School constructed in Instagram gained 20 test items categorized in medium level of difficulty which is appropriate to be used, (4) The English Vocabulary test for 10th grade students of Vocational High School constructed in Instagram meet the characteristics of interactive, interesting, and visual-based.